STRATEGY FOR INCREASING THE FINANCIAL PERFORMANCE OF CULINARY MSMEs IN THE POST-PANDEMI COVID-19 ERA IN JAMBI CITY - Mugi Rahayu; Fitriaty Fitriaty; Idham Khalik (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
Abstract The purpose of this study is to analyze strategies for improving the financial performance of Culinary MSMEs in the current era and after the Covid-19 pandemic in Jambi City. The analysis tools used are SWOT analysis and PLS analysis. The results showed that the SO (Strenght Opportunity) Strategy increased customer trust, added employees, and maintained cleanliness. The WO (Weaknesses Opportunity) strategy provides discounts on every purchase, providing free order delivery services at short distances. Strategy ST (Strenght Threat) adding new employees, decorating the room so that visitors are comfortable. The WT (Weaknesses Threat) strategy is adding new products or adding level variants to old products, looking for new investors to expand the business. Then Entrepreneur Orientation has a significant effect on innovation in Culinary MSMEs in Jambi City, Market Orientation has no significant effect on innovation in Culinary MSMEs in Jambi City, Entrepreneur Orientation has a significant effect on Financial Performance on Culinary MSMEs in Jambi City, Market Orientation has no significant effect on Financial Performance on Culinary MSMEs in Jambi City, Innovation has a significant effect on Financial Performance on Culinary MSMEs in Jambi City, Entrepreneurial Orientation has a significant effect on MSME Financial Performance with innovation as a mediating variable on Culinary MSMEs in Jambi City, Market Orientation has a significant effect on MSME Financial Performance with innovation as a mediating variable in Culinary MSMEs in Jambi City. Keywords: Financial Performance, Innovation, SWOT.